2015
DOI: 10.1007/s10658-015-0679-7
|View full text |Cite
|
Sign up to set email alerts
|

The origin of reactive oxygen during interaction of Pinus sylvestris root and Heterobasidion annosum s.l. – the linkage with the iron

Abstract: Reactive oxygen species (ROS) can be promoted differently, although iron is regarded as a condicio sine qua of their generation. We assessed how enzymes involved in ROS production and iron accumulation impact the interactions between Pinus sylvestris root and p at ho g e ns w i t h di ff e r e n t ho s t pr ef e r e n ce s (Heterobasidion annosum sensu stricto, H. parviporum and H. abietinum). Studies with inhibitors of ROS generation showed that diphenylene iodonium (DPI) and potassium cyanide (KCN) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 56 publications
0
6
1
Order By: Relevance
“…Use of CCA method enable to graphically extent interpretation of results obtained during experiment in case when observations are classified according to experimental factors. In another paper [27] positions of the pathogen isolates were presented graphically according to their differences in accumulation of reactive oxygen for data set undergoing one-way classification. In two years of studies on differences in visible tobacco leaf injury the use of CCA gave opportunity to arrange experimental objects according to rural and urban sites [28].…”
Section: Discussionmentioning
confidence: 99%
“…Use of CCA method enable to graphically extent interpretation of results obtained during experiment in case when observations are classified according to experimental factors. In another paper [27] positions of the pathogen isolates were presented graphically according to their differences in accumulation of reactive oxygen for data set undergoing one-way classification. In two years of studies on differences in visible tobacco leaf injury the use of CCA gave opportunity to arrange experimental objects according to rural and urban sites [28].…”
Section: Discussionmentioning
confidence: 99%
“…ROS are involved at the initial stage of a plant's response to necrotrophic pathogens and mycorrhizal fungus colonization. There is growing evidence that iron may also be one of the essential factors regulating plant-fungal interactions (Expert and O'Brian 2012;Johnson et al 2007;Mucha et al 2012Mucha et al , 2015. Whether the role of iron is linked to the role of ROS generation and whether a linkage of iron and ROS to host response is dependent on the trophic strategy of the invading fungus are still not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous results demonstrated that a hypersensitive response related to Fe and H 2 O 2 can regulate the initial stage of P. sylvestris root infection by the pathogen, Heterobasidion annosum s.s. (Mucha et al 2012). It was subsequently demonstrated that an iron-dependent mechanism primarily operates in the meristematic zone of P. sylvestris roots invaded by H. annosum s.s., and to a much lesser extent, in roots invaded by pathogens (H. parviporum and H. abietinum) that are more atypical for P. sylvestris (Mucha et al 2015). It is unclear, however, whether iron levels, and its distribution in different root zones, is another factor that impacts the redox state in trophically diverse fungusplant root interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations of the interaction effects between levels of two factors revealed a tendency when considering class (cell) means. Use Canonical variate analysis can be applied to other kinds of data matrix, such as matrices of one-way classification (Mucha et al 2015), two-way classification with one observation per cell (Kayzer et al 1999, block designs (Lejeune 2000) and other factorial designs (Budka et al 2015). Canonical variate analysis is similar to another procedure called principal component analysis.…”
Section: Asmentioning
confidence: 99%